Afghan Health Related Concerns Following the US Withdrawal: Results of a Survey Given via Social Media - Shah, Jaffer; Shah, Asghar; Tokhi, Ahmad Fahim; Shedrow, Jordan; Hernandez, Nicolas; Varney, Joseph; Qaderi, Pashton; Masoumi, Seyed Javad; Qaderi, Shohra (Frontiers in Public Health, 2022)
Background The United States Armed Forces completed their withdrawal from Afghanistan on August 30th, 2021, ending 20 years of war in Afghanistan. This rapid timeline from announcement to withdrawal and subsequent power transfer had profound consequences on the Afghan people, particularly in the domains of health and healthcare. Methods On 15 September 2021, we posted an anonymous online cross-sectional survey on social media (Twitter, Facebook, and WhatsApp groups) to collect data about respondents from Afghanistan. Questions focused on COVID-19 symptoms, concerns, and individual care with a focus on changes related to the United States (US) withdrawal from Afghanistan. The form was composed of 17 questions which included multiple choice, single choice, and numeric options. All questions were optional including demographic data. Results Our survey yielded 1,074 responses from the Farsi version and 572 responses from the Pashto version for a total of 1,646 responses. 1,286 (80%) of respondents were in Afghanistan at the time of survey submission. Concerning the US withdrawal from Afghanistan, 26% (412) respondents were extremely concerned and 12% (181) were moderately concerned. A majority of respondents report concerns regarding mental health due to the US withdrawal. 27% (418) report extreme concern, 12% (186) report moderate concern, and 15% (229) report a little concern. There is a significant difference in the proportions of concern (for US withdrawal generally, as well as physical and mental health) across gender. 49% of Female respondents report extreme concern regarding the US withdrawal compared to 22% of Male respondents (P < 0.001). With respect to physical health concerns 36% of Females report extreme concern compared to 16% of Males (P < 0.001). Finally on the mental health concerns, 54% of Females report extreme concern compared to 22% of Males (P < 0.001). Conclusion The results from this survey are susceptible to the possibility of internal validity and/or external validity. However, we are accepting of those possibilities considering this survey wasn't designed to be bulletproof, but rather serve as a voice for those who can't be heard and to inform the public of the hardships occurring across the globe due to a steadfast retraction of the US footprint from their soil. Our findings indicate salient changes and public health concerns among Afghans following the US withdrawal from the region. These concerns varied across gender and ethnic groups. Our findings may serve as the first step in addressing the health concerns of Afghans following two decades of US military presence. The results should be understood through the limitations associated with a survey study design. Future research and policy aimed at tackling short and long-term health and social concerns in Afghanistan should consider the role of US withdrawal.